(untitled) (Research, Society and Development, 2023)
Objective: To provide an overview of breast cancer detection methods, the challenges faced, and future prospects in the early detection of this disease. Methodology: This study is framed as a narrative literature review with qualitative exploratory characteristics. Results and Discussion: Mammography is the most widely used and proven effective method for early detection of breast cancer, especially in older women. In addition to this method, recent advancements in medical technology have led to the development of other breast cancer detection techniques such as breast magnetic resonance imaging, ultrasound, and digital breast tomosynthesis. Conclusion: Early detection of breast cancer is of utmost importance to increase the chances of cure and improve treatment outcomes. The combination of different detection methods and regular follow-up with healthcare professionals are essential to ensure early detection and appropriate treatment of breast cancer.